Who is to Blame on July 22, 2011? Psychological and Sociological Blame Frames in the Reporting of Anders Breivik in the Dutch Speaking Broadsheet Press - Mertens, Stefan (International Studies. Interdisciplinary Political and Cultural Journal, 2015)
On July 22, 2011 Anders Breivik murdered a large amount of people in Norway. In this study we investigate a sample of articles that were published about Breivik and his deeds in the Flemish and Dutch press. We will investigate these articles looking for the so-called “attribution of responsibility frame.” The murders from Breivik could be explained psychologically (“he is insane”) as well as sociologically (far-right political parties are responsible because of having spread hate speech). We present a typology of subtypes of frames. We will furthermore investigate how many times these types of frames occur in different media outlets.